Plastid Genomes and Proteins Illuminate the Evolution of Eustigmatophyte Algae and Their Bacterial Endosymbionts - Ševcíková, Tereza; Yurchenko, Tatiana; Fawley, Karen P; Amaral, Raquel; Strnad, Hynek; Santos, Lilia M A; Fawley, Marvin W; Eliáš, Marek (Genome biology and evolution, 2019)
Eustigmatophytes, a class of stramenopile algae (ochrophytes), include not only the extensively studied biotechnologically important genus Nannochloropsis but also a rapidly expanding diversity of lineages with much less well characterized biology. Recent discoveries have led to exciting additions to our knowledge about eustigmatophytes. Some proved to harbor bacterial endosymbionts representing a novel genus, Candidatus Phycorickettsia, and an operon of unclear function (ebo) obtained by horizontal gene transfer from the endosymbiont lineage was found in the plastid genomes of still other eustigmatophytes. To shed more light on the latter event, as well as to generally improve our understanding of the eustigmatophyte evolutionary history, we sequenced plastid genomes of seven phylogenetically diverse representatives (including new isolates representing undescribed taxa). A phylogenomic analysis of plastid genome-encoded proteins resolved the phylogenetic relationships among the main eustigmatophyte lineages and provided a framework for the interpretation of plastid gene gains and losses in the group. The ebo operon gain was inferred to have probably occurred within the order Eustigmatales, after the divergence of the two basalmost lineages (a newly discovered hitherto undescribed strain and the Pseudellipsoidion group). When looking for nuclear genes potentially compensating for plastid gene losses, we noticed a gene for a plastid-targeted acyl carrier protein that was apparently acquired by horizontal gene transfer from Phycorickettsia. The presence of this gene in all eustigmatophytes studied, including representatives of both principal clades (Eustigmatales and Goniochloridales), is a genetic footprint indicating that the eustigmatophyte-Phycorickettsia partnership started no later than in the last eustigmatophyte common ancestor.
Keywords: symbióza; sekvence aminokyselin; operon; Stramenopiles; Genome, Plastid; genom plastidový; Amino Acid Sequence; Symbiosis; biologická evoluce; Biological Evolution; Rickettsiaceae; Heterokontophyta; Operon